Tackling irrigation development and water management crises in Africa - Zemadim, Birhanu; Haileslassie, Amare; Dirwai, Tinashe Lindel; Gebrezgabher, Solomie A.; Akpoti, Komlavi; Osei-Amponsah, Charity; Cofie, Olufunke O.; Hafeez, Mohsin; Smith, Mark (International Water Management Institute, 2025)
Water management presents significant challenges in Africa due to problems that link food security, poverty, ecosystem degradation, population growth, urbanization, and climate change, each influencing the other. Central to this is the challenge of irrigation development, including inadequate infrastructure, poor operational and maintenance practices, and limited access to innovative solutions in public sector-led schemes. The need for large-scale irrigation infrastructure in Africa persists and is likely to increase in the coming decades. In most cases, the actual size of state-led irrigable land realized has been significantly smaller than planned, resulting in smaller plot allocations than theoretically thought possible. This has negatively impacted poverty alleviation and food security efforts, where farmer-led irrigation development (FLID) is only beginning to emerge. Significant areas with irrigation infrastructure are only discontinuously cultivated in most places, while others are permanently abandoned. Many irrigation schemes continue to operate below capacity due to inadequate operation and maintenance frameworks, misaligned institutional mandates, and limited farmer engagement. In transboundary cases, documented evidence suggests investing in a win-win regional policy approach to foster cooperation and integration at the national scale across economic communities. If implemented successfully, this effort will increase and enhance opportunities for developing cascaded irrigation systems and realizing irrigation potential at multiple scales—across formal and informal irrigation subsectors. Addressing Africa’s irrigation development and water management crises requires an integrated approach that combines technological innovation, robust policy reforms, and farmer-led or community-driven water stewardship, with a focus on inclusion to build resilience against the impacts of climate variability.